Task-Based Learning Used in Teaching Speaking at Senior High School - Faisal Anam; Siti Maria Ulfa; Moh. Hafidz (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2021)
The study aims to describe the implementation of task based learning in teaching speaking and students’ responses toward the use of task based learning to teaching speaking in Senior High School. The research design of the study was descriptive qualitative. It involved a video from YouTube that relate with the title of the study. The title of the video is Implementasi Kurikulum 2013 Saintifik - Bahasa Inggris SMA/MA” ( Implementation of the 2013 Scientific Curriculum - English Subject of Senior High School/MA” ) in the YouTube channel “Dunia Belajar 86”. From the video that had been observed by the researcher, it can be concluded that Task-Based Learning was highly influential in teaching speaking skills as it could be seen from students’ responses and enthusiasm in participating in the learning activities. Further, the teacher provided a lot of stimulation in the form of media and questions that made the students feel more interested in the subject being taught.